2016
DOI: 10.1016/j.jempfin.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A fractionally cointegrated VAR model with deterministic trends and application to commodity futures markets

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…Even though there is evidence of long memory in the basis or forward premiums in currency markets (Baillie and Bollerslev, 1994), equity markets (Lien and Tse, 1999) and commodity markets (Dolatabadi et al, 2014), fractional cointegration in prices (which are typically I(1)) is not considered. 10 Lien and Tse (1999) show that the relative size between a VECM MVHR and a Fractional-VECM MVHR is indeterminable in practice, and that a Fractional-VECM GARCH hedge performs no better than a VECM-GARCH hedge over 1 to 40 day horizons.…”
Section: Model Extensionsmentioning
confidence: 99%
“…Even though there is evidence of long memory in the basis or forward premiums in currency markets (Baillie and Bollerslev, 1994), equity markets (Lien and Tse, 1999) and commodity markets (Dolatabadi et al, 2014), fractional cointegration in prices (which are typically I(1)) is not considered. 10 Lien and Tse (1999) show that the relative size between a VECM MVHR and a Fractional-VECM MVHR is indeterminable in practice, and that a Fractional-VECM GARCH hedge performs no better than a VECM-GARCH hedge over 1 to 40 day horizons.…”
Section: Model Extensionsmentioning
confidence: 99%
“…This fractionally cointegrated equilibrium model is suggested by Dolatabadi, Nielsen, and Xu (2014) (henceforth DNX), and is briefly reviewed in Section 2.3 below. DNX apply this model to analyze the fractional cointegration relationship empirically using the FG data set within the FCVAR model.…”
Section: Introductionmentioning
confidence: 99%
“…Our empirical work applies the version of the FCVAR model given in (5) and we provide comparisons with the CVAR model in (6). The asymptotic analysis of the FCVAR model is provided in Nielsen (2010, 2012), where it is shown that the maximum likelihood estimator of (b; ; 1 ; : : : ; k ) is asymptotically normal, while the maximum likelihood estimator of ( ; ) is asymptotically mixed normal when b > 1=2 and asymptotically normal when b < 1=2.…”
Section: The Fcvar Model and Interpretationmentioning
confidence: 99%
“…The forecastability of commodity market returns is a very active area of research in financial economics. In particular, recent research has shown that commodity spot and futures prices are fractionally cointegrated: see, inter alia, Baillie and Bollerslev (1994), Lien and Tse (1999), Maynard and Phillips (2001), Coakley, Dollery, and Kellard (2011), and Dolatabadi, Nielsen, and Xu (2016. An implication is that a fractionally cointegrated model may provide a better statistical fit for commodity prices and returns.…”
Section: Introductionmentioning
confidence: 99%